Cuidados de enfermería en la disminución de casos de hiperbilirrubinemia en recién nacidos del servicio de neonatología del Hospital Alfredo Noboa Montenegro en el periodo octubre 2018 – abril 2019 - Barragán Barrezueta, Luiggy Fabrizzio (2019)
Nursing care is vital for the recovery of hospitalized patients; such nursing care is often undervalued even by the nursing staff itself, which is why this research project is being developed to respond to the problem. How do nursing care reduce cases of hyperbilirubinemia in newborns of the neonatology service of the Alfredo Noboa Montenegro Hospital in the period October 2018 - April 2019? since one of the most frequent disorders of neonatal age is hyperbilirubinemia, representing the most common cause of hospital readmission in the first week of life, being a challenge especially due to early discharge. The objective of the research is to identify the nursing care that contributes to the decrease of cases of hyperbilirubinemia in newborns of the neonatology service of the Alfredo Noboa Montenegro Hospital in the period October 2018 - April 2019. To raise awareness of the importance of nursing care by following established protocols with updated scientific content, especially in neonatology. Inductive, deductive and synthesis methods of transversal type are used, thus allowing to analyze and describe the collected information. The results obtained through the use of observation sheets and surveys show that the nursing staff of the neonatology service of the Alfredo Noboa Montenegro Hospital is qualified to provide adequate nursing care to neonates with hyperbilirubinemia, despite not having an institutional protocol for the application of phototherapy. It is concluded that it has been possible to verify that the fulfillment of the norms and protocols in the nursing care contributes to the decrease of cases of hyperbilirubinemia in newborns of the neonatology service of the Hospital Alfredo Noboa Montenegro in the period October 2018 - April 2019 being vital in the recovery of the newborns with hyperbilirubinemia thus preventing the re-admission of the patients